2002
DOI: 10.1902/jop.2002.73.10.1126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recombinant Human Bone Morphogenetic Protein‐4 on the Osteoblastic Differentiation of Mouse Calvarial Cells Affected by Porphyromonas gingivalis

Abstract: Our results suggest that supplemental BMPs would be beneficial for improved treatment of osseous defects, although their biologic effect might be significantly reduced by periodontopathic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The factor within the matrix responsible for this effect was later named BMP. After recombinant human BMP(rhBMP) was successfully synthesized by Wozney et al [2] in 1988, a number of studies have demonstrated the biologic activities of rhBMPs which include the induction of ectopic cartilage and bone formation at implanted sites in vivo [2][3][4] and the stimulation of osteoblastic phenotype expression, such as alkaline phosphatase (ALP), type I collagen, osteocalcin (OC), osteopontin (OP) and bone sialoprotein during the course of osteoblastic differentiation in various types of cells in vitro [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The factor within the matrix responsible for this effect was later named BMP. After recombinant human BMP(rhBMP) was successfully synthesized by Wozney et al [2] in 1988, a number of studies have demonstrated the biologic activities of rhBMPs which include the induction of ectopic cartilage and bone formation at implanted sites in vivo [2][3][4] and the stimulation of osteoblastic phenotype expression, such as alkaline phosphatase (ALP), type I collagen, osteocalcin (OC), osteopontin (OP) and bone sialoprotein during the course of osteoblastic differentiation in various types of cells in vitro [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human bone morphogenetic proteins (rhBMPs) have been shown to possess significant osteoinductive potential [1][2][3][4][5][6], but in order to take advantage of this effect for tissue engineering, carrier systems are essential [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies included the induction of ectopic cartilage and bone formation at implanted sites in vivo [2][3][4] and the stimulation of osteoblastic phenotype expression during the course of osteoblastic differentiation in various cell types in vitro. [5][6][7][8][9] Currently, >20 BMPs have been identified, and several, including BMP-2, -4, -5, -6, and -7, have been shown to have significant osteoinductive activity. [6][7][8][9][10][11][12][13][14] Accordingly, there have been many trials using rhBMPs for bone tissue engineering.…”
mentioning
confidence: 99%